2020
DOI: 10.1371/journal.pone.0228346
|View full text |Cite
|
Sign up to set email alerts
|

Spatial and temporal distribution of dengue in Brazil, 1990 - 2017

Abstract: Dengue is a viral disease caused by an arbovirus of the genus Flavivirus transmitted in Brazil by the mosquito Aedes aegypti (Linnaeus, 1762). Simultaneous circulation of the four viral serotypes (DENV1, 2, 3 and 4) has been occurring since 2010 and determines a scenario of hyperendemicity of the disease in the country. This study aimed to describe the epidemiological situation of dengue in Brazil in the last three decades. This is a descriptive, observational study that used data of dengue notifications of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
28
0
7

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(40 citation statements)
references
References 31 publications
2
28
0
7
Order By: Relevance
“…In the analyzed period, 509 261 cases of dengue were confirmed in the Northeast, an incidence rate of 224 cases per 100 000 inhabitants. This result is close to that found in a study carried out in Brazil between 1990 and 2017, which found an incidence rate for the northeast region of 246 cases per 100 000 inhabitants (Table 1 ) [ 7 ]. The semiarid climate, which is predominant in the Northeast, combined with poor sociodemographic conditions may contribute to the high rates of dengue in this region [ 28 ].…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…In the analyzed period, 509 261 cases of dengue were confirmed in the Northeast, an incidence rate of 224 cases per 100 000 inhabitants. This result is close to that found in a study carried out in Brazil between 1990 and 2017, which found an incidence rate for the northeast region of 246 cases per 100 000 inhabitants (Table 1 ) [ 7 ]. The semiarid climate, which is predominant in the Northeast, combined with poor sociodemographic conditions may contribute to the high rates of dengue in this region [ 28 ].…”
Section: Discussionsupporting
confidence: 90%
“…The year 2015 was responsible for the majority of cases registered in the period (43.2%) (Table 1 ). This year was marked by one of the largest dengue epidemics that Brazil has ever had, with 1 688 688 cases recorded, an incidence of 826 cases per 100 000 inhabitants, and co-circulation of the four DENV serotypes [ 7 , 10 ]. On the other hand, in 2017 there was a drastic reduction in dengue incidence compared to previous years.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Dengue virus (DENV) has been endemic in the northeastern region of Brazil for over 30 years, with circulation of the four serotypes (DENV 1–4), causing a significant number of cases and several outbreaks in all states of the region [ 1 , 2 ]. The chikungunya virus (CHIKV) was detected in the Americas in 2014 [ 3 ] and caused a major epidemic in 2017 with approximately 190,000 cases reported in Brazil, with 173 deaths, according the SINAN (Portuguese acronym for Notifiable Diseases Information System, official epidemiologic suveilance).…”
Section: Introductionmentioning
confidence: 99%
“…Dengue fever (DF) is an arthropod‐borne infection; however, dengue viruses 1‐4 (DENV 1‐4) can also be transmitted by blood transfusion 1‐3 . DF is a public health issue in Brazil, where the number of suspected cases corresponded to 55% of the 18 million cases reported across the American continent between 1995 and 2015 4 . In 2019, a total of 1 544 987 cases were reported in the country, an increase of almost six times over that observed in 2018 5 .…”
mentioning
confidence: 99%